A HYBRID FINITE DIFFERENCES, AND CHARGE SIMULATION METHOD FOR THE COMPUTATION OF HIGH VOLTAGE ELECTRIC FIELDS - Hoffmann, J. N. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A new treatment is proposed to the hybrid method of Finite Differences and Charge Simulation for the computation os electric fields, entirely applicable to the similar hybrid method of Finite Element and Charge Simulation. The resulting system of linear equations is solved by using the fixed point theory, the QR decomposition and the Conjugate Gradients Squared method with a preconditioning technique. New procedures are suggested for the discretization of the boundary conditions, which lead to results with higher precision. Case studies are included. [Vol. 12, No. 1 (1997), Special Issue on International Computational Electromagnetics, pp 103-110]